Combined aerobic/inspiratory muscle training vs. aerobic training in patients with chronic heart failure. (14th March 2014) - Adamopoulos, Stamatis; Schmid, Jean‐Paul; Dendale, Paul; Poerschke, Daniel; Hansen, Dominique; Dritsas, Athanasios; Kouloubinis, Alexandros; Alders, Toon; Gkouziouta, Aggeliki; Reyckers, Ilse; Vartela, Vasiliki; Plessas, Nikos; et al.
<x xml:space="preserve">Abstract</x> Aims Vent‐HeFT is a multicentre randomized trial designed to investigate the potential additive benefits of inspiratory muscle training (IMT) on aerobic training (AT) in patients with chronic heart failure (CHF). Methods and results Forty‐three CHF patients with a mean age of 58 ± 12 years, peak oxygen consumption (peak VO2) 17.9 ± 5 mL/kg/min, and LVEF 29.5 ± 5% were randomized to an AT/IMT group (n = 21) or to an AT/SHAM group (n = 22) in a 12‐week exercise programme. AT involved 45 min of ergometer training at 70–80% of maximum heart rate, three times a week for both groups. In the AT/IMT group, IMT was performed at 60% of sustained maximal inspiratory pressure (SPImax) while in the AT/SHAM group it was performed at 10% of SPImax, using a computer biofeedback trainer for 30 min, three times a week. At baseline and at 3 months, patients were evaluated for exercise capacity, lung function, inspiratory muscle strength (PImax) and work capacity (SPImax), quality of life (QoL), LVEF and LV diameter, dyspnoea, C‐reactive protein (CRP), and NT‐proBNP. IMT resulted in a significantly higher benefit in SPImax (P = 0.02), QoL (P = 0.002), dyspnoea (P = 0.004), CRP (P = 0.03), and NT‐proBNP (P = 0.004). In both AT/IMT and AT/SHAM groups PImax (P < 0.001, P = 0.02), peak VO2 (P = 0.008, P = 0.04), and LVEF (P = 0.005, P = 0.002) improved significantly; however, without an additional benefit for either of the groups. Conclusion This randomized multicentre study demonstrates that IMT combined with aerobic training provides additional benefits in functional and serum biomarkers in patients with moderate CHF. These findings advocate for application of IMT in cardiac rehabilitation programmes.